Treatment and regimen change in a cohort of HIV positive patients in anti-retroviral treatment at Tshepang Wellness Clinic, Dr George Mukhari Hospital - Moeketsi, Ntshebo Mirriam (University of Limpopo ( Medunsa Campus ), 2010)
Background: Antiretroviral therapy led to a revolution in care of patients with HIV/AIDS in a developed world. Treatment is not a cure but it also presented with new challenges of side effects, drug resistance and it also dramatically reduces rate of mortality and morbidity and it also improves quality of life to people living with HIV/AIDS, and it also now considered as manageable chronic diseases. Aim: Aim of the study is to establish and describe reasons for treatment and regimen change in a cohort of HIV positive patients on ART enrolled in the pharmaco-epidemiological survey at Tshepang wellness clinic. Objectives: is to determine reasons for treatment and regimen change, types of treatment and regimen change among patients on ART who are enrolled in pharmacoepidemiological survey at Tshepang wellness clinic. Design and Methods: Study is a retrospective cohort study, and sample size of 301 medical records of a cohort of HIV positive patients on ARVs enrolled in a longitudinal pharmaco-epidemiological survey from November 2006-May 2007 reviewed. Data extraction tool used to collect data and software called SPSS 17.0 used to analyze data and relevant themes were extracted to determine distribution of variables. Results: Results of this study indicated that 91 (85%) were males and (87.8%) 191 were females. Age was grouped as teenagers (15-25yrs), young adults (26-49yrs) and adults (50- 70yrs). Results also shows reasons of treatment and regimen change of which majority of patients 134(44.8%) changed due toxicity followed by 16 (5.4%) who changed because of pregnancy, and the other 4(1.3%) changed because of resistance, and the last 2(0.7%) which are regarded as minorities change because of T.B. Conclusion and Recommendations: Results shows that majority of pharmacovigilance patients were initiated Regimen 1 compared to other regimens. Toxicity appear as the main reason of treatment and regimen change on this study as 140(46.4%) reported toxicities (peripheral neuropathy, lactic acidosis, lipodystrophy and lipoatrophy). Implementation of monitoring of adherence needed for prevention of resistance and virological failure.
Thesis (MPH)--University of Limpopo, 2010.
Keywords: HIV/AIDS; Antiretroviral therapy